2012
DOI: 10.1097/jto.0b013e318241655f
|View full text |Cite
|
Sign up to set email alerts
|

c-MET/Phospho-MET Protein Expression and MET Gene Copy Number in Non-small Cell Lung Carcinomas

Abstract: c-MET/phospho-MET expression and MET BISH positivity differed according to histological type. Among ADCs, c-MET expression and MET BISH positivity were more common in poorly differentiated cases. MET BISH positivity was an independent prognostic factor in nonsquamous NSCLCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
3
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 32 publications
(49 reference statements)
12
98
3
4
Order By: Relevance
“…As a result, MET protein overexpression in unselected NSCLC cases has been reported to range from 20% to 70%. 137,138 An MA has found that MET expression by IHC in NSCLC is a negative prognostic factor in patients with surgically resected NSCLC. 107 A frequently used commercially available antibody, particularly in clinical trials, is the CONFIRM anti-total MET (SP44) rabbit monoclonal primary antibody (Ventana Medical Systems, Tucson, Arizona) directed against a membranous and cytoplasmic epitope of MET.…”
Section: Lung Cancer Molecular Testing Guideline Updatementioning
confidence: 99%
“…As a result, MET protein overexpression in unselected NSCLC cases has been reported to range from 20% to 70%. 137,138 An MA has found that MET expression by IHC in NSCLC is a negative prognostic factor in patients with surgically resected NSCLC. 107 A frequently used commercially available antibody, particularly in clinical trials, is the CONFIRM anti-total MET (SP44) rabbit monoclonal primary antibody (Ventana Medical Systems, Tucson, Arizona) directed against a membranous and cytoplasmic epitope of MET.…”
Section: Lung Cancer Molecular Testing Guideline Updatementioning
confidence: 99%
“…Moreover, it is notable that all three of these mechanisms of MET/MET dysregulation have been documented in non-small cell lung cancer (NSCLC; refs. [19][20][21][22]. Early studies established that MET can be overexpressed or activated [as measured by phosphorylation of the catalytic domain as well as juxtamembrane (JM) domain], or the gene mutated (in the semaphorin or JM domains) and/or amplified in lung cancer.…”
Section: Hfg/met In Lung Cancermentioning
confidence: 99%
“…26 The oncogenic dysregulation of the HGF/c-MET pathway has been implicated in a wide range of human epithelial cancers including liver, lung, colorectal, breast, pancreatic, ovarian, prostate, hepatic, and gastric cancers. [27][28][29][30][31] This pathway results in cell survival and migration and tumor development and progression. 27,32 c-Met over-activation occurs via several molecular mechanisms, including gene amplification, 31 overexpression, 33 mutations, 34 or RTK transactivation or changes in ligandinduced autocrine or paracrine signaling; 35 all of them have been reported in several human tumor types.…”
Section: Aberrant C-met Signaling In Crcmentioning
confidence: 99%